Carbapenem-Resistant Gram-Negative Bacilli Characterization in a Tertiary Care Center from El Bajio, Mexico - Jose Raul Nieto-Saucedo; Luis Esaú López-Jacome; Rafael Franco-Cendejas; Claudia Adriana Colín-Castro; Melissa Hernández-Duran; Luis Raúl Rivera-Garay; Karina Senyase Zamarripa-Martinez; Juan Luis Mosqueda-Gómez (MDPI AG, 2023)
Carbapenem-resistant Gram-negative bacilli (CR-GNB) are a major public health concern. We aimed to evaluate the prevalence of CR-GNB and the frequency of carbapenemase-encoding genes in a tertiary referral center from El Bajio, Mexico. A cross-sectional study was conducted between January and October 2022; Gram-negative bacilli (GNB) were screened for in vitro resistance to at least one carbapenem. CR-GNB were further analyzed for carbapenemase-production through phenotypical methods and by real-time PCR for the following genes: blaKPC, blaGES, blaNDM, blaVIM, blaIMP, and blaOXA-48. In total, 37 out of 508 GNB were carbapenem-resistant (7.3%, 95% CI 5.2-9.9). Non-fermenters had higher rates of carbapenem resistance than Enterobacterales (32.5% vs. 2.6%; OR 18.3, 95% CI 8.5-39, p < 0.0001), and Enterobacter cloacae showed higher carbapenem resistance than other Enterobacterales (27% vs. 1.4%; OR 25.9, 95% CI 6.9-95, p < 0.0001). Only 15 (40.5%) CR-GNB had a carbapenemase-encoding gene; Enterobacterales were more likely to have a carbapenemase-encoding gene than non-fermenters (63.6% vs. 30.8%, p = 0.08); blaNDM-1 and blaNDM-5 were the main genes found in Enterobacterales; and blaIMP-75 was the most common for Pseudomonas aeruginosa. The mcr-2 gene was harbored in one polymyxin-resistant E. cloacae. In our setting, NDM was the most common carbapenemase; however, less than half of the CR-GNB showed a carbapenemase-encoding gene.